Are you sure you got everything here correct?
Because the way things are presented, if you could get (x+6) = 0 or sqrt (9-x^2) = 0 then the whole thing would be zero.
So the first part x + 6 = 0 gives x = -6
In the second part 9 - x^2 = 0 gives x = +/- 3
Hope this helps, I will check back later for additional comments.
2007-01-31 05:46:39
·
answer #1
·
answered by nicewknd 5
·
0⤊
0⤋
If a*b = 0, then either a = 0 or b = 0 (or both). The only way to multiply 2 numbers and get 0 is for one (or both) to be zero. Therefore:
x+6 = 0 or 9-x^2 = 0
a) x + 6 = 0, x = -6
b) 9-x^2 = 0, x = -3 or 3
So your solution is x = -6, -3, or 3
Hope this helps! :)
2007-01-31 13:48:59
·
answer #2
·
answered by disposable_hero_too 6
·
0⤊
0⤋
One of your terms, x+6 or sqrt (9-x^2), must equal zero.
0 = n * m, n or m or both equal zero
where n=x + 6 and m=sqrt(9 - x^2)
solve for n=0
x + 6 =0
x = -6
solve for m=0
sqrt(9 - x^2) = 0
9 - x^2 = 0; squared both sides
9 = x^2
sqrt(9)= x
x = |3|; x equals 3 or -3
the valid answers for x are 3, -3 and -6
2007-01-31 13:50:12
·
answer #3
·
answered by Greg H 3
·
0⤊
0⤋